O niektórych teoretycznych aspektach nauczania literatury w Niemieckiej Republice Demokratycznej = About some theoretical aspects of teaching literature in the German Democratic Republic - Jonas, Hartmut (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper treats of the theoretical output of literary didactics in the German Democratic Republic. According to the author the scientific research concentrates on the following points:l. problems of literary and aesthetic reception, 2. influence of a literary work, 3. possibility of individuals-creation inherent in a literary work, 4. social functions of literature, 5. dialectal connections between the process of creation and the reception. The most important task of literary didactics is its moulding as an independent scientific discipline.
Keywords: literatura; nauczanie; Niemiecka Republika Demokratyczna